Coronary angiography Review of 1500 consecutive cases. Issue 11 (November 1976) - Pridie, R B; Booth, E; Garrett, J; Knight, E; Parnell, B; Towers, M K
Abstract : Fifteen hundred coronary angiograms have been performed by the staff of Harefield Hospital since 1970. Only 2 deaths have occurred in the last 1000 consecutive cases though there were 5 in the first 500 cases. This drop in the mortality is ascribed to careful attention to detail and better training of the operators. It is concluded that the Fudkin's method of coronary angiography in trained hands is a safe method of investigation but that because of the very serious potential dangers it is unjustifiable for new units to start unless there is a fully experienced investigator in charge.